Identification, Characterization, and In Silico Analysis of New Imine Reductases From Native Streptomyces Genomes - Iglesias, César; Tijman, Ariel; López, Gonzalo; Lapaz, María Inés; Pianzzola, María Julia; Panizza, Paola; Rodríguez Giordano, Sonia (Frontiers in Catalysis, 2021)
The development of biocatalytic tools for the synthesis of optically pure amines has been the focus of abundant research in recent years. Among other enzymes, imine reductases have attracted a lot of attention associated to the possibility of attaining chiral secondary amines. Furthermore, the reductive aminase activity associated with some of these enzymes has facilitated the production of optically pure amines from a prochiral ketone, a transformation that opens doors to an incredible array of products. In this work, the genomes from native Streptomyces strains isolated in our lab have been explored on the search for novel imine reductases. Application of different structural criteria and sequence motif filters allowed the identification of two novel enzymes, Ss-IRED_S and Ss-IRED_R. While the former presented outstanding activity towards bulky cyclic imine substrates, the latter presented reductive aminase activity with the assayed ketones. A bioinformatic analysis based on modelling and docking studies was performed in order to explain the differences in enzyme activity, searching for additional criteria that could be used to analyse enzyme candidates in silico, providing additional tools for enzyme selection for a particular application. Our findings suggest that imine reductase activity could be predicted by this analysis; overall, accounting for the number of docking positions that meet the catalytic requirements.